Evaluasi Alinyemen Vertikal dan Horizontal Studi Kasus di Depan Gedung Perpustakaan Kampus Dramaga IPB - Chasanah, Khuswatun; Purwanto, Moh. Yanuar Jarwadi; Sudibyo, Tri (Departemen Teknik Sipil dan Lingkungan IPB, 2018)
Campus Library IPB Dramaga has a fairly sharp bend with a limited curved radius, causing the vehicle must be careful when passing even with low speed, especially the medium-size vehicles. The purpose of this research was to evaluate vertical and horizontal alignment in front of library building based on RSNI T-14-2004. The result showed that the road geometric design did not conform to the SNI, especially the horizontal alignment, whereas the vertical alignment did not need to be evaluated. With a plan speed of 30 km/h and vehicle slow down of 3.4 m/s2, the persistent visibility was 35 m. The minimum bend radius for all bends was 36.8 m, while the existing radius at A1, A2, B1, B2, B3, and B4 were 17 m, 22 m, 10 m, 16 m, 6.4 m, and 9 m respectively. Using the rotary radius to allow the vehicle to pass safely, the minimum radius at B3 and B4 at the intersection was 7.3 m.